Operation Solomon: Mass Evacuation of Ethiopian Jews, A Constructivism Approach on International Relations - Najmuddin, Moh; Hayatullah, Imam Khomaeni (Journal of Social Dynamics and Governance, 2024)
This article examines Operation Solomon (1991), an intelligence operation by the Israeli government to bring Ethiopian Jews to Israel. Ethiopian Jews are a community that has been in Ethiopia for thousands of years but maintains its religious traditions and dreams of returning to the promised land in Palestine. As a Zionist state, Israel saw the suffering of Ethiopian Jews during the Ethiopian Civil War as a reason to evacuate them to Israel. The relationship between Israel and Ethiopian Jews was strengthened by Alexander Wendt’s Constructivism theory which states that intersubjective understanding is the main driving force in a country’s foreign policy. Israel received support from American Jews and successfully carried out Operation Solomon after conducting negotiations with the Ethiopian government